Comparative analysis of interference, noise and losses in the mobile communication systems in millimeter wave range - Кременецька, Яна; Марков, Сергій; Kremenetskaya, Yana; Markov, Sergey (Lviv Politechnic Publishing House, 2018)
Проаналізовано підходи до математичного моделю- вання мобільних систем у міліметровому діапазоні хвиль. Розглянуто архітектуру мобільної мережі з використанням технології Radio over Fiber (радіо по волокну), запро- поновану для формування і передавання сигналів міліметрового діапазону через волоконно-оптичні лінії. Проаналізовано шуми оптичного гетеродинування, що застосовують для формування радіосигналів. Проведено математичний аналіз складових енергетичного бюджету радіолінії в міліметровому діапазоні на основі дослідження фундаментальних фізичних аспектів, що впливають на значення шумів, втрат і підсилень сигналу. Виконано порівняльний аналіз показників співвідношеннь сигнал/ інтерференція та сигнал/шум. Запропоновано квазіоптичну модель конусоподібного випромінювання антени для розрахунків шумових завад і втрат сигналу в багатопро- меневих моделях поширення з урахуванням множинних відображень і дифракцій, а також поглинання у різних середовищах. З аналізу складових енергетичного бюджету радіолінії в міліметровому діапазоні випливає, що необхідно в моделях покриття мобільних систем враховувати як за- лежність від інтерференційних завад, так і шуми, пов’язані з методом генерації, випромінювання сигналів, а також ефекти молекулярного поглинання (повторного випро- мінювання) в атмосфері й ефекти відображення сигналів у міській забудові.

The article analyzes the approaches to the mathematical modeling of mobile systems in the millimeter wave range. The architecture of a mobile network using Radio over Fiber (RoF) technology is considered which is proposed for forming and transmitting the millimeter-wave signals via fiber-optic communication lines. The noise of the optical heterodyne used for the formation of radio signals is analyzed. The mathematical analysis of the components of the energy budget of the radio link in the millimeter wave range is carried out on the basis of a study of the fundamental physical aspects that affect the value of noise, losses and signal gains. The comparative analysis of the signal-to-interference ratio and the signal-to-noise ratio, the probability of transmitting information radio signals through the reflected paths is carried out. A quasi-optical model of the narrow-beam antenna radiation is proposed for calculating noise interference and signal loss in multipath propagation models taking into account multiple reflections and diffractions, as well as absorption in various media. The analysis of the energy budget components of the radio link in the millimeter wave range shows that it is necessary to take into account both interference and noise associated with the method of signal generation and emission, for example, in phased antenna arrays, as well as the effects of molecular absorption (repeated radiation) in the atmosphere and the effects of the reflection of signals in urban scenario.
Порівняльний аналіз інтерференції, шуму і втрат в мобільних системах зв’язку міліметрового діапазону хвиль
Keywords: millimeter wave range; wireless communication; noise regime; directional antennas; interference; radio link energy budget; RoF technology; signal to interference ratio; signal to noise ratio